Last year, sales at a book store increased from $5,000 to $10,000. This year, sales decreased to $5,000 from $10,000. What percentage did sales increase last year? What percentage did sales decrease this year?

Answers

Answer 1
Answer:

Solution:

we are given that

Last year, sales at a book store increased from $5,000 to $10,000.

As we know that percentage increase is given by the formula

Percentage increase=(change)/(Initial)*100

Substitute the values we get

Percentage increase=(10000-5000)/(5000)*100

Percentage increase =(5000)/(5000)*100=100%.

This year, sales decreased to $5,000 from $10,000.

Percentage Decrease =(change)/(Initial)*100

Substitute the values we get

Percentage Decrease =(10000-5000)/(10000)*100

Percentage Decrease=(5000)/(10000)*100=50%.

Answer 2
Answer:

Answer:

100%, 50%

Step-by-step explanation:


Related Questions

In 195019501950, the per capita gross domestic product (GDP) of Australia was approximately \$1800$1800dollar sign, 1800. Each year afterwards, the per capita GDP increased by approximately 6.7\%6.7%6, point, 7, percent. Write a function that gives the approximate per capita GDP G(t)G(t)G, left parenthesis, t, right parenthesis of Australia ttt years after 195019501950. Do not enter commas in your answer.
Suppose you place 16 green, 25 blue, and 9 yellow marbles in a non-transparent bag. you then randomize the marbles by shaking them up thoroughly. assume you then randomly select two marbles from the bag without replacement. what is the probability of selecting two blue marbles?
7. In right triangle BCD, BD12, mLC 90, andmLDBC47. Find DC to the nearest tenth47
Subtract.(x + 1) - (-2x - 5) A) 6 –x B) -x - 4 C) 3x - 4 D) 3x + 6
Rearrange to make a the subject:v=u+at

Zina spends 1.5 hours setting up her sewing machine and making one hat. The total amount of time spent making hats can be represented by the sequence below.1.5, 2.25, 3.0, 3.75, ...

Which recursive formula can be used to determine the total amount of time spent making hats based on the total amount of time spent previously?

A. f(n + 1) = f(n) + 1.5
B. f(n + 1) = f(n) + 0.75
C. f(n + 1) = f(n)
D. f(n + 1) = f(n)

Answers

Let

f(1)=1.5\n f(2)=2.25\n f(3)=3\n f(4)=3.75

we know that

f(2)-f(1)=2.25-1.5=0.75\n f(2)=f(1)+0.75\n \n f(3)-f(2)=3-2.25=0.75\n f(3)=f(2)+0.75\n \n f(4)-f(3)=3.75-3=0.75\n f(4)=f(3)+0.75\n \n.\n.\n.\n f(n+1)=f(n)+0.75

This is an arithmetic sequence, the common difference is equal to 0.75

therefore

the answer is the option

B. f(n + 1) = f(n) + 0.75

It would be f(n+1) = f(n)+0.75

So, OPTION B IS YOUR ANSWER.........

What is the solution of the system? Use substitution. 3x + 2y = 7
y = –3x + 11
A.
(6, -3)

B.
(6, -7)


D.
(5, -4)

C:

Answers

Hi Brainiac


3x+2y=7

y=-3x+11


We need to solve y=-3x+11 for y

Now let's start by substitute -3x+11 for y in 3x+2y=7

3x+2y=7

3x+2(-3x+11)=7

-3x+22=7

Now add -22 to both sides

-3x+22-22=7-22

-3x=-15

To find the value for x we need to divide both sides by -3

-3x/-3= -15/-3

x=5

Now we have the value for x :)

Let's find the value for y by substitute 5 for x in y=-3x+11

y=-3x+11

y=-3(5)+11

y=-4

Here you go :)

The answer is D


Good luck :0

PLEASE HELP!!! 20 POINTS! FAKE RESPONSES REPORTED

Answers

Answer:

118 degrees

Step-by-step explanation:

quadrilaterals add up to 360

NMQ is 62 degrees so MPQ must be too

62 x 2=124   360-124=236

236/2=118

<NPQ = <NMQ i believe, making it so that <NPQ is 62 degrease

What is the factored form of 6x^2 + 13x + 6?A.) (x + 4)(x + 9)
B.) (2x + 3)(3x + 2)
C.) (2x + 6)(3x + 1)
D.) (6x + 1)(6x + 1)

Answers

The answer would be B.first you would have to multiply the first coefficient,6 with the last term. being 6,                                                                                                   6·6 = 36.Now there is a few factors such as 1,2,3,4,6,9,12,18,36, and the negatives of these numbers, but i wont list them,i will just use the numbers i need for this problem.so i will replace the number 13 in this equation.              [6ײ+4×]+[9×+6]. then i will factor the GCF 2 into the first group and then factor 3 in the second group. 2×[3×+2]+3·[3×+2]. then i would have to factor out the two numbers out of the term 3×+2 then combine the like terms making the equation [2×+3]·[3×+2] making the answer B. Hope i helped bye.

The correct answer is option B.) (2x + 3)(3x + 2).

Given that the factored form of 6x^2 + 13x + 6 is equivalent to which of the following.

A.) (x + 4)(x + 9)

B.) (2x + 3)(3x + 2)

C.) (2x + 6)(3x + 1)

D.) (6x + 1)(6x + 1)

To determine the factored form of the quadratic expression 6x^2 + 13x + 6, we can apply the factoring technique. We are looking for two binomials in the form (px + q)(rx + s) that, when multiplied, result in the original expression.

To factor the expression, we need to find two numbers whose product is equal to 6 * 6 = 36 and whose sum is equal to 13.

The numbers that satisfy these conditions are 4 and 9.

Therefore, the factored form of the expression is:

(2x + 3)(3x + 2)

So, the correct answer is option B.) (2x + 3)(3x + 2).

Learn more about factoring quadratic expressions click here: brainly.com/question/14680354

#SPJ6

PQR is shown.
What are the missing side lengths in PQR?
Please try to show your work

Answers

The triangle is isosceles. It also has two 45 degree angles. That means the sides are "x" and the hypotenuse is sqrt(2)*x. If you do the math, the answer is 8.485

What decimal is written in words “five and four hundred sixty-seven ten thousandths”? a. 5.467

b. 5.0467

c. 5,647,000

d. 0.5467

Answers

Answer:

five and four hundred sixty-seven ten thousandths

b. 5.0467

0.

0   tenths

0   hundreds

0   thousands

0   ten thousands

~batmans wife dun dun dun....

     

~batmans wife dun dun dun....